STUDI RETROSPEKTIF PENGGUNAAN TRIHEXYFENIDIL PADA PASIEN SKIZOFRENIA RAWAT INAP YANG MENDAPAT TERAPI ANTIPSKOTIK DI RUMAH SAKIT JIWA SAMBANG LIHUM - Anggie Rahaya; Noor Cahaya (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2016)
Trihexyphenidyl (THP) is used to treat symptoms of Parkinson's disease or involuntary movements due to the side effects of certain psychiatric drugs. It can also decrease other side effects such as muscle stiffness/rigidity (extrapyramidal syndrome or EPS). EPS were an unavoidable consequence of effective antipsychotic therapy. EPS reduce beneficial effects of antipsychotic treatment on the negative, cognitive, and mood symptom domains, while increasing the risk of tardive dyskinesia and reducing compliance. The purpose of this research was to analyze the percentage use of THP and the pattern of THP usage on schizophrenia patient which treated at Sambang Lihum Hospital. This retrospective observational study was conducted at an inpatient Sambang Lihum Hospital. This research were conducted to 264 medical records of patients period January 2013 to December 2013 which receive antipsychotics medication. Data were analyzed by univariate analysis. The result showed 94.32% (n=264) received THP. This research has shown the pattern of THP usage in Sambang Lihum Hospital which was to give THP directly to patients without EPS examination is 96.79% (n=249) and there are 15.66% (n=249) patients evaluated after 14 days after THP administered. Key Words: Schizophrenia, Trihexyphenidyl, EPS